2020
DOI: 10.31234/osf.io/4r3mh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of natural environment on mental health: an umbrella review of systematic reviews and meta-analyses

Abstract: Objectives: To synthesize the evidence on the effects of exposure to natural environment on mental health to inform future policymaking, practice, and research. Methods: A systematic search of nine major databases and additional sources were conducted using relevant keywords for the natural environment and mental health till November 2019. We included systematic reviews or meta-analyses reporting any measures of associations between the natural environment and mental health. The data on study characteristics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…These results also support Hypothesis 2 in this study, saying that video from the forest areas reduces short-term procrastination more, than the video from an urban area. Previous studies have shown that psychological well-being can be increased through the impact of the forest environment [43,65,75], including in a virtual form [59]. Current research has shown that fluid procrastination can also be changed by representing the natural environment in the form of a video film.…”
Section: The Impact Of the Forest Environment On The Level Of Procrasmentioning
confidence: 99%
“…These results also support Hypothesis 2 in this study, saying that video from the forest areas reduces short-term procrastination more, than the video from an urban area. Previous studies have shown that psychological well-being can be increased through the impact of the forest environment [43,65,75], including in a virtual form [59]. Current research has shown that fluid procrastination can also be changed by representing the natural environment in the form of a video film.…”
Section: The Impact Of the Forest Environment On The Level Of Procrasmentioning
confidence: 99%
“…Since 2015, many umbrella reviews have been conducted to evaluate the evidence base on the psychosocial epidemiology of mental health in diverse populations [22][23][24][25][26][27]. Although several reviews have reported psychological impacts of quarantine or isolation [28,29], no umbrella review or overview of the reviews was found, although such a review could provide valuable information on the mental health implications of quarantine and isolation within the global landscape.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2015, many umbrella reviews have been conducted evaluating the evidence base on the psychosocial epidemiology of mental health in diverse populations [19][20][21][22][23][24]. However, no umbrella review or review of the reviews was found, which can inform the mental health implications of quarantine and isolation for infection prevention at the global landscape.…”
Section: Introductionmentioning
confidence: 99%